ANALIS EKSPERIMENTAL SOLAR WATER HEATER TRICKLE SYSTEM DENGAN V BERHIMPIT LAJU ALIRAN 3 LPM - Andi Dwi Saputro Saputro; Nugroho Agung Pambudi; Yuyun Estriyanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
The purpose of this study was to determine the efficiency of the performance of a solar water heater with V coincides with variations in flow rates of  3 lpm, .This research is a quantitative research with experimental method. This research includes the activities of designing a solar water heater, preparing measuring instruments, testing, collecting data and analyzing data. This research was replicated three times to obtain maximum data results. The results showed that the solar water heater testing with a flow rate variation of 3 lpm experienced the highest temperature increase, the amount of solar radiation and wind speed greatly influenced changes in temperature. The conclusion of this study is the greater the flow rate used, the smaller the temperature change produced and at a flow rate of 3lpm is the most effective flow rate, indicated by an energy efficiency value of 78%.